Das Erwachen des Kentauren - Sylvia Kratochvil (Recherches Germaniques)
This article deals with the figure of the Centaur in Hölderlin’s later poetry. The constellation of this figure is based on the Ode Chiron introducing the Night Songs as well as on its earlier version, The Blind Singer. There are equally two fragments by Pindar that Hölderlin translated and commented on: Untreue der Weisheit and Das Belebende. An early fragment by Walter Benjamin brings us closer to Hölderlin’s figure. Chiron, who distinguished himself among the Centaurs, forms an anthropological center around which Walter Benjamin’s philosophy of history revolves.